Reforming the Legal Framework of Notary Supervision in Indonesia: Towards a Digital Governance Model - Dwi Suryahartati; Jefri Mahardika (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2025)
The supervision of notaries in Indonesia remains conventional, mainly relying on manual, hierarchical, and fragmented mechanisms that hinder transparency, efficiency, and accountability. In contrast, many jurisdictions have restructured their professional oversight through digital governance systems to promote integrity and responsiveness in public services. Although Law No. 30 of 2004 and Law No. 2 of 2014 provide a normative foundation for notary supervision, Indonesia lacks operational mechanisms and digital integration consistent with global governance standards. Reforming this system has therefore become crucial to align national practices with international developments in digital legal oversight. This study employs a normative juridical method combined with conceptual and comparative approaches. Legal materials, including statutory provisions, academic journals, and institutional reports, were analyzed to identify structural and normative weaknesses. Comparative insights from the Netherlands, Germany, and the United States reveal that digital supervision enhances transparency, professional ethics, and institutional accountability. The findings show that Indonesia’s three-tier supervisory structure—MPD, MPW, and MPP—is legally established but technologically outdated. This research proposes a digital governance model for notary supervision integrating electronic supervision, real-time data reporting, and inter-institutional connectivity. Embedding responsive law principles, the model contributes to the global discourse on digital legal governance by providing a context-sensitive framework for modernizing professional oversight in developing legal systems.